Quality of life evaluation study for caregivers of patients undergoing enteral tube feeding at home (Annals of Medical Research, 2021)
Aim: Care burden in patients undergoing enteral tube feeding at home reduces the quality of life their caregivers. Quality of life for caregiver, an integral part of a good homecare, has not been adequate researched with regard to quantity and attribution. Material and Methods: A quantitative sample was created totally 95 primary caregivers of patients undergoing more than one year enteral tube feeding. Quality of life measurement was done with Rolls Royce Quality of Life Scale. The data was evaluated Kruskal-Wallis test and t-test.Results: In this study was determined that demographic data have 81% were female, 22% illiterate. 96% caregivers lived together in the same home with the patient, 64% have children. The data significant lowness all the quality of life dimensions; also mean ± standard deviation was defined as 102.05±23.49(min 42, max 170).Conclusion: It was obtained evidence relating to caregivers of patients undergoing enteral tube feeding at home have low quality of life.Keywords: Caregivers; Enteral Nutrition; Enteral Tube Feeding; Quality of Life.